Edgardo Cadlum was appointed principal of the grade school - De La Salle College (Animo Repository, 1976)
Edgardo Cadlum was appointed Principal of the Grade School effective school year 1976-1977. He is the first layman to occupy the position. Ms. Josefina Alburo, former grades 1 to 4 vice-principal, is now over-all Vice Principal.1976